Exosome‐Coated Zeolitic Imidazolate Framework Nanoparticles for Intracellular Detection of ATP†. Issue 8 (7th June 2021) - Lv, Wenxing; Han, Ziwei; Li, Yike; Huang, Yanjuan; Sun, Jiashu; Lu, Xiaoquan; Liu, Chao
Main observation and conclusion: The intracellular delivery of metal‐organic frameworks (MOFs) encapsulated with functional biomolecules represents a promising avenue in the field of biomedicine and biosensing. To improve the cellular uptake efficiency of MOFs, here we report the fabrication of cancer cell‐derived exosome membrane (EM)‐coated zeolitic imidazolate framework‐8 (EM‐ZIF‐8) nanoparticles by using a microfluidic sonication device. EM‐ZIF‐8 nanoparticles loaded with FITC‐labeled bovine serum albumin (BSA) can be taken up by cancer cells and evade phagocytosis more efficiently than their counterparts (ZIF‐8 nanoparticles). Moreover, we use EM‐ZIF‐8 loaded with Rhodamine B (RhB) for in situ imaging of cellular adenosine triphosphate (ATP). The shield effect of ZIF‐8 suppresses the fluorescence of RhB, and the presence of ATP disrupts the ZIF‐8 structure based on the competitive coordination between ATP and Zn 2+, leading to the restoration of RhB fluorescence. This method allows accurate detection of the fluctuation of ATP in A549 cells induced by Ca 2+ or 2‐DDG treatment. The devised biomimetic EM‐ZIF‐8 nanoparticles thus provide an efficient platform for intracellular drug delivery and ATP sensing. Abstract : Exosome membrane‐coated zeolitic imidazolate framework‐8 (EM‐ZIF‐8) nanoparticles are fabricated through a microfluidic sonication approach. The devised biomimetic EM‐ZIF‐8 nanoparticles are a highly efficient platform for intracellular drug delivery and ATP sensing.